Steel material with excellent workability and its manufacturing method
A steel material with a specific composition and processing method achieves a balance between hardness and workability, addressing the challenges faced by existing tool steel materials by ensuring excellent processability and high hardness properties.
Patent Information
- Application Number
- JP2022536689
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-20
- Filing Date
- 2020-12-16
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-12-16
AI Technical Summary
Existing steel materials for tool applications face challenges in achieving a balance between hardness and workability, particularly due to the difficulty in ensuring high hardness while maintaining sufficient processability, especially in high carbon steel.
A steel material with a composition of C: 0.8-1.0%, Si: 0.1-0.3%, Mn: 0.2-0.5%, Cr: 0.1-0.3%, P: 0.03% or less, S: 0.005% or less, and the balance Fe and other inevitable impurities, featuring a ferrite single-phase structure with spheroidized carbides, is developed. This material is processed through reheating, hot rolling, winding, and segmenting carbides using mechanical forces, followed by spheroidization annealing.
The resulting steel material exhibits excellent workability, with a surface hardness of 230-270 HV, a burr height of 20 μm or less after pressing, and a bending workability of 2 or less, while also achieving a surface hardness of 56HRC or more after heat treatment.
Smart Images

Figure 0007662643000003 
Figure 0007662643000004 
Figure 0007662643000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a steel material which has excellent workability and is particularly suitable as a tool material, and a method for producing the same. [Background technology]
[0002] In general, it is widely known that it is difficult to achieve both hardness and workability in the physical properties of steel. This is because an increase in the strength of steel increases its hardness, but as the strength of steel increases, its workability decreases.
[0003] Tool steels used in the manufacture of tool parts also require excellent workability when they are manufactured into part shapes, while the parts after final machining require high hardness in order to ensure wear resistance, impact resistance, etc. In particular, tool steels used in the manufacture of tool parts mainly contain a relatively large amount of carbon (C) in order to ensure a certain level of hardness and strength, making it difficult to ensure the desired level of workability.
[0004] In the case of tool steel, a common method is to ensure the workability of the steel by spheroidizing annealing, process it into a part shape, and then quench it to introduce a martensite structure into the steel to ensure hardness. Spheroidizing annealing is a heat treatment carried out at high temperatures to make plate-shaped lamellar cementite into a spheroidal shape, and since it takes a long time to ensure the desired level of workability, it is undesirable from the standpoints of productivity and economy.
[0005] In Patent Document 1, in order to shorten the annealing heat treatment time, annealing heat treatment process conditions are proposed in which heat treatment is performed for a short time at a temperature equal to or higher than A1, and then heat treatment is performed for a long time at a temperature lower than A1. However, such a heating pattern is not only difficult to realize using a normal heating furnace, but also has the problem that it still takes a long time to ensure the workability of high carbon steel. Therefore, it is not desirable as a practical method for manufacturing high carbon tool steel. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Korean Patent Publication No. 10-2015-0075290 Summary of the Invention [Problem to be solved by the invention]
[0007] According to one aspect of the present invention, a steel material having excellent workability and a manufacturing method thereof can be provided.
[0008] The subject of the present invention is not limited to the above content, and a person skilled in the art will have no difficulty in understanding additional subjects of the present invention from the overall content of this specification. [Means for solving the problem]
[0009] According to one aspect of the present invention, a steel material having excellent workability contains, by weight, 0.8 to 1.0% C, 0.1 to 0.3% Si, 0.2 to 0.5% Mn, 0.1 to 0.3% Cr, 0.03% or less P, 0.005% or less S, the balance being Fe and other inevitable impurities, and the microstructure is a ferritic single-phase structure containing spheroidized carbides, the average grain size of the carbides is 0.8 μm or less, and the number density of the carbides is 2*10 5 ~7*10 5 pieces / mm 2 It may be.
[0010] The spheroidization rate of the carbide may be 95% or more.
[0011] The room temperature surface hardness of the steel material may be 230 to 270 HV.
[0012] The steel material may have a burr height of 20 μm or less after press working, and a bending workability (R / t) of 2 or less.
[0013] The average grain size of the carbide may be 0.55 μm or more.
[0014] The steel material may have a surface hardness of 56HRC or more after being heated to 800 to 950°C, maintained at that temperature for 30 minutes or less, cooled to a temperature range of 50°C or less at a cooling rate of 50 to 150°C / s, and heat-treated at 200 to 300°C for 10 to 60 minutes.
[0015] According to another aspect of the present invention, a method for producing a steel material with excellent workability includes the steps of reheating, hot rolling, and coiling a slab containing, by weight, 0.8-1.0% C, 0.1-0.3% Si, 0.2-0.5% Mn, 0.1-0.3% Cr, 0.03% or less P, 0.005% or less S, with the balance being Fe and other unavoidable impurities; applying a mechanical external force to the coiled steel material to segment carbides in the steel material; and heating the steel material with the segmented carbides, and then maintaining the temperature in the range of 650-700°C for 5-20 hours to perform spheroidizing annealing.
[0016] In the step of segmenting the carbides, the coiled steel material can be cold-rolled at a rolling reduction of 30 to 50% to segment the carbides of the steel material.
[0017] The slab can be reheated in a temperature range of 1000 to 1300°C, the reheated slab can be hot rolled in a temperature range of 850 to 1150°C, and the hot rolled steel material can be coiled in a temperature range of 600 to 650°C. Effect of the Invention
[0018] According to a preferred aspect of the present invention, it is possible to provide a tool steel material having excellent hardness characteristics as well as excellent workability, and a method for producing the same. [Brief description of the drawings]
[0019] [Figure 1] 1 is a photograph showing the microstructure of test piece A. [Diagram 2] 1 is a photograph showing the microstructure of test piece H. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention relates to a steel material having excellent workability and a manufacturing method thereof, and preferred embodiments of the present invention will be described below. The embodiments of the present invention can be modified in various forms, and the scope of the present invention should not be interpreted as being limited to the embodiments described below. The present embodiments are provided to provide the present invention in more detail to those skilled in the art to which the present invention pertains.
[0021] Hereinafter, the steel material having excellent workability as one aspect of the present invention will be described in more detail.
[0022] According to one aspect of the present invention, a steel material having excellent workability contains, by weight, 0.8 to 1.0% C, 0.1 to 0.3% Si, 0.2 to 0.5% Mn, 0.1 to 0.3% Cr, 0.03% or less P, 0.005% or less S, the balance being Fe and other inevitable impurities, the microstructure is a ferritic single-phase structure containing spheroidized carbides, the average grain size of the carbides is 0.8 μm or less, and the number density of the carbides is 2*10 5 ~7*10 5 pieces / mm 2 It may be.
[0023] The alloy composition of the present invention will be described in detail below. Unless otherwise specified, % and ppm of the content of the alloy composition are based on weight.
[0024] According to one aspect of the present invention, a steel material having excellent workability contains, by weight percent, 0.8-1.0% C, 0.1-0.3% Si, 0.2-0.5% Mn, 0.1-0.3% Cr, 0.03% or less P, 0.005% or less S, with the balance being Fe and other unavoidable impurities.
[0025] Carbon (C): 0.8~1.0% Carbon (C) is a representative element that contributes to improving hardenability, and in the present invention, it is an essential element added to ensure hardness after quenching. Therefore, in the present invention, 0.8% or more of carbon (C) can be included to achieve this effect. A preferred carbon (C) content may be more than 0.8%, and a more preferred carbon (C) content may be 0.82% or more. On the other hand, if the carbon (C) content in steel exceeds a certain range, the proportion of carbides in the steel becomes excessively high, which may promote brittle fracture. Therefore, in the present invention, the upper limit of the carbon (C) content may be limited to 1.0%. A preferred carbon (C) content may be less than 1.0%, and a more preferred carbon (C) content may be 0.98% or less.
[0026] Silicon (Si): 0.1-0.3% Silicon (Si) is a component that contributes to improving the strength of steel. Therefore, in the present invention, in order to achieve this effect, silicon (Si) of 0.1% or more can be included. A preferred lower limit of the silicon (Si) content is 0.12%, and a more preferred lower limit of the silicon (Si) content is 0.15%. However, if the silicon (Si) content in steel exceeds a certain range, not only the cold rolling property is reduced, but also decarburization is likely to occur during heat treatment, which may induce an increase in surface scale defects on the surface of the steel material. Therefore, in the present invention, the upper limit of the silicon (Si) content can be limited to 0.3%. A preferred upper limit of the silicon (Si) content can be 0.28%, and a more preferred upper limit of the silicon (Si) content can be 0.25%.
[0027] Manganese (Mn): 0.2-0.5% Manganese (Mn) is an element that not only contributes to improving hardenability, but also effectively contributes to improving the strength of steel through solid solution strengthening. In addition, manganese (Mn) combines with sulfur (S) in steel to precipitate as MnS, so that red shortness caused by sulfur (S) can be effectively prevented. In the present invention, manganese (Mn) can be contained in an amount of 0.2% or more to achieve such an effect. A preferable lower limit of the manganese (Mn) content is 0.25%, and a more preferable lower limit of the manganese (Mn) content is 0.3%. However, if the manganese (Mn) content in the steel exceeds a certain range, not only the cold rolling property is deteriorated, but also the workability may be deteriorated due to center segregation. Therefore, in the present invention, the upper limit of the manganese (Mn) content can be limited to 0.5%. A preferable upper limit of the manganese (Mn) content is 0.45%, and a more preferable upper limit of the manganese (Mn) content is 0.4%.
[0028] Chromium (Cr): 0.1-0.3% Chromium (Cr) is an element that effectively contributes to improving hardenability, similar to manganese (Mn). Therefore, in the present invention, chromium (Cr) can be contained in an amount of 0.1% or more for this effect. The lower limit of the chromium (Cr) content is preferably 0.13%, and more preferably 0.16%. However, if the chromium (Cr) content in the steel exceeds a certain range, not only is there a risk of deterioration in cold rolling properties, but the decomposition of carbides by heat treatment is delayed, and spheroidization of carbides may not be completed even by spheroidization annealing. Therefore, in the present invention, the upper limit of the chromium (Cr) content can be limited to 0.3%. The upper limit of the chromium (Cr) content is preferably 0.28%, and more preferably 0.25%.
[0029] Phosphorus (P): 0.03% or less (including 0%) Phosphorus (P) is a typical impurity element in steel, but it does not significantly impair formability and is the most advantageous element for ensuring strength. However, if phosphorus (P) is added in excess, it increases the possibility of brittle fracture, which may not only induce sheet breakage of the slab during hot rolling, but may also significantly deteriorate the surface properties of the plated steel sheet. Therefore, in the present invention, the upper limit of the phosphorus (P) content can be limited to 0.03%.
[0030] Sulfur (S): 0.005% or less (including 0%) Sulfur (S) is an impurity element that is inevitably mixed into steel, and it is preferable to control its content as low as possible. In particular, since sulfur (S) in steel may induce red shortness, in the present invention, the upper limit of the sulfur (S) content can be limited to 0.005%.
[0031] According to one aspect of the present invention, the steel material having excellent workability may contain the balance Fe and other inevitable impurities in addition to the above-mentioned components. However, in a normal manufacturing process, unintended impurities may be inevitably mixed in from the raw materials or the surrounding environment, and therefore, it is not possible to completely exclude them. These impurities are well known to anyone having ordinary knowledge in this technical field, and therefore, the entire contents of them will not be specifically mentioned in this specification. However, the addition of effective components other than the above-mentioned composition is not excluded.
[0032] According to one aspect of the present invention, the microstructure of the steel material may be a ferrite single-phase structure containing spheroidized carbides. The spheroidized carbides of the present invention include not only the case where all the carbides are spheroidized, but also the case where some of the carbides are spheroidized. The average grain size of the carbides is 0.8 μm or less, and the number density of the carbides is 2*10 5 ~7*10 5 pieces / mm 2 That is, according to one aspect of the present invention, the steel material has not only finely formed spheroidized carbides in the steel but also a large amount of carbides uniformly distributed therein, so that the workability of the steel material can be effectively ensured.
[0033] According to one aspect of the present invention, the carbides contained in the steel material may have a spheroidization rate of 95% or more, and the spheroidization rate of the preferred carbides may be 99% or more. Here, the spheroidization rate of the carbides means the ratio of the area of spheroidized carbides having an aspect ratio (ratio of major axis to minor axis) of 2 or less to the area of all carbides. In other words, according to one aspect of the present invention, most of the carbides contained in the steel material are spheroidized carbides, so that the workability of the steel material can be effectively ensured.
[0034] Furthermore, when the average grain size of the carbides contained in the above steel material is below a certain level, this means that the carbides are not sufficiently spheroidized, so in the present invention, the lower limit of the average grain size of the carbides can be limited to 0.55 μm.
[0035] According to one aspect of the present invention, the room temperature surface hardness of the steel material may be 230 to 270 HV. According to another aspect of the present invention, the steel material having excellent workability may have a burr height of 20 μm or less after press working, and the bending workability (R / t) of the steel material may be 2 or less. The burr height can be determined by measuring the difference in height of the surface edge with a roughness measuring device after blanking processing under a condition of a clearance of 5°. The bending workability can be measured by whether or not cracks occur on the surface of the material when the material is bent 90° while being pressed with a triangular prism of cemented carbide having a radius of curvature R (mm) at the end portion. In the bending workability, t means the thickness (mm) of the steel material.
[0036] According to one aspect of the present invention, the steel material may have a surface hardness of 56HRC or more after being subjected to a process in which the above-mentioned steel material is heated to 800 to 950°C, maintained at that temperature for 30 minutes or less, cooled at a cooling rate of 50 to 150°C / s to a temperature range of 50°C or less, and heat-treated at 200 to 300°C for 10 to 60 minutes. That is, according to one aspect of the present invention, the steel material can ensure excellent workability before quenching and can ensure excellent hardness characteristics after quenching.
[0037] Hereinafter, as one aspect of the present invention, a method for producing a steel material having excellent workability will be described in more detail.
[0038] According to one aspect of the present invention, a method for producing a steel material with excellent workability includes the steps of reheating, hot rolling, and coiling a slab containing, by weight, 0.8-1.0% C, 0.1-0.3% Si, 0.2-0.5% Mn, 0.1-0.3% Cr, 0.03% or less P, 0.005% or less S, with the balance being Fe and other unavoidable impurities; applying a mechanical external force to the coiled steel material to segment carbides in the steel material; and heating the steel material with the segmented carbides, and then maintaining the temperature in the range of 650-700°C for 5-20 hours to perform spheroidizing annealing.
[0039] (slab reheating, hot rolling, and coiling) After preparing a slab having a predetermined alloy composition, reheating can be performed. Since the alloy composition of the slab of the present invention corresponds to the alloy composition of the steel material described above, the description of the alloy composition of the slab of the present invention is replaced with the description of the alloy composition of the steel material described above. In addition, the reheating temperature of the slab of the present invention can be the same as the conditions applied to the reheating of a normal slab, and as a non-limiting example, the reheating temperature of the slab in the present invention may be in the range of 1000 to 1300°C.
[0040] The reheated slab is hot-rolled in a temperature range of 850 to 1150°C to provide a hot-rolled steel material. If the hot-rolling temperature is too high, the microstructure becomes coarse, and the desired physical properties cannot be ensured. Therefore, in the present invention, the upper limit of the hot-rolling temperature range can be limited to 1150°C. On the other hand, if the hot-rolling temperature is below a certain level, excessive rolling load can become a problem, and therefore, in the present invention, the lower limit of the hot-rolling temperature can be limited to 850°C.
[0041] The hot-rolled steel material can be coiled at a temperature range of 600 to 650°C. If the coiling temperature is too high, not only will the thickness of cementite in the pearlite structure increase, but there is also a risk of shape defects occurring due to phase transformation after coiling. Therefore, in the present invention, the upper limit of the coiling temperature can be limited to 650°C. On the other hand, if the coiling temperature is below a certain level, the strength is too high and there is a concern of sheet breakage in the process after coiling. Therefore, in the present invention, the lower limit of the coiling temperature can be limited to 600°C. In addition, in order to prevent sheet breakage due to material deviation in the carbide segmentation stage described below, the temperature deviation in the longitudinal direction of the entire length of the hot-rolled coil can be controlled to 20°C or less.
[0042] (Carbide Segmentation by Application of External Mechanical Force) After the coiled steel material is unwound, a pickling process can be selectively applied depending on the surface quality of the unwound steel material, and then a mechanical external force can be applied to the steel material to mechanically segment the carbides (lamellar cementite). Any method can be used to apply a mechanical external force to the steel material as long as it can segment the lamellar cementite, and as a non-limiting example, cold rolling or forging can be applied. As an example, when applying a mechanical external force to the steel material by applying cold rolling, a cold reduction rate of 30 to 50% can be applied in consideration of effective segmentation of cementite.
[0043] In the present invention, a mechanical external force is applied to the hot-rolled steel material to segment lamellar cementite, so that the spheroidizing efficiency in the subsequent spheroidizing annealing can be effectively improved. That is, in the present invention, since the spheroidizing annealing is started in a state in which finely segmented carbides are distributed in large amounts, the carbides can be effectively spheroidized within a relatively short time.
[0044] (Spheroidizing annealing) The steel material in which the carbides have been segmented by the application of a mechanical external force can be heated in a temperature range of 650 to 700°C and maintained for 5 to 20 hours to perform spheroidizing annealing. If the temperature and time of spheroidizing annealing are below a certain level, the carbides may not be sufficiently spheroidized, and therefore, in the present invention, the lower limits of the temperature and time of spheroidizing annealing can be limited to 650°C and 5 hours, respectively. On the other hand, if the temperature and time of spheroidizing annealing exceed a certain level, not only the carbides may become excessively coarse, but also there is a concern that the hardness of the steel material may decrease, and therefore, in the present invention, the upper limits of the temperature and time of spheroidizing annealing can be limited to 700°C and 20 hours, respectively.
[0045] The microstructure of the steel material produced by the above-mentioned production method may be a ferritic single-phase structure containing spheroidized carbides. The average grain size of the carbides may be 0.55 μm or more, and the spheroidization rate of the carbides may be 95% or more.
[0046] The steel material produced by the above-mentioned production method may have a room temperature surface hardness of 230 to 270 HV, a burr height of 20 μm or less after press working, and a bending workability (R / t) of 2 or less. EXAMPLES
[0047] The present invention will be described in more detail below with reference to examples. However, it should be noted that the examples described below are merely intended to illustrate and further embody the present invention, and are not intended to limit the scope of the present invention.
[0048] (Example) After preparing a slab consisting of the alloy composition in Table 1, it was heated in the temperature range of 1200 ° C and hot rolled in the temperature range of 950 ° C. After pickling, it was cold rolled at a rolling reduction of 50% and rolled into a thin steel plate with a thickness of 1.0 mm. The rolling properties during cold rolling were evaluated for each steel type, and are shown in Table 1. When no plate breakage or edge cracks occurred during cold rolling, or when edge cracks occurred but the number of cracks was less than 5 and the size was less than 10 mm, it was evaluated as "○". In addition, when plate breakage and edge cracks occurred during cold rolling, and the size of the edge cracks was 10 mm or more, or the number of cracks was 5 or more and the size was less than 10 mm, it was evaluated as "X".
[0049] [Table 1]
[0050] Thereafter, spheroidizing annealing was performed under the conditions shown in Table 2, and the hardness and microstructure of each test piece were compared and analyzed, and the results are shown in Table 2. However, test piece K means a test piece that was immediately subjected to spheroidizing annealing without cold rolling. At this time, the hardness of each test piece was measured in HRC using a Brinell hardness tester and converted to HV. In addition, for the microstructure of each test piece, the test piece was cut and mirror-polished, then etched, and the cross-sectional structure was observed using a scanning electron microscope. In addition, after pressing each test piece under a clearance of 5%, the height of the burr was measured, and a 90° bending test was performed to measure the bending workability (R / t). In addition, each test piece was subjected to a quenching treatment in which it was heated to a temperature of 900°C and rapidly cooled, and a tempering treatment in which it was heated to a temperature of 250°C, and then the surface hardness was measured. These results are also shown in Table 2. The surface hardness at this time was also measured in HRC using a Brinell hardness tester.
[0051] [Table 2]
[0052] It was confirmed that all test pieces satisfying all of the alloy composition and process conditions limited by the present invention were able to secure excellent hardness characteristics and workability, whereas test pieces not satisfying any one of the alloy composition and process conditions limited by the present invention were unable to secure both the hardness characteristics and workability at the levels targeted by the present invention.
[0053] Figure 1 is a photograph of the microstructure of test piece A, from which it can be seen that fine spheroidized carbides are uniformly distributed in large quantities. In contrast, Figure 2 is a photograph of the microstructure of test piece H, from which it can be seen that not only is the spheroidization rate of carbides low, but that coarse carbides are also distributed locally.
[0054] Although the present invention has been described in detail with reference to the above exemplary embodiments, other embodiments may be possible, and therefore the spirit and scope of the appended claims should not be limited to the above exemplary embodiments.
Claims
1. In weight percent, it contains C: 0.8-1.0%, Si: 0.1-0.3%, Mn: 0.2-0.5%, Cr: 0.1-0.3%, P: 0.03% or less, and S: 0.005% or less, with the balance being Fe and other inevitable impurities; The microstructure is a single-phase ferrite structure containing spheroidized carbides, The carbide having a grain size of 150 nm or more has an average grain size of 0.8 μm or less, The number density of the carbides having a grain size of 150 nm or more is 2*10 5 ~7*10 5 pieces / mm 2 It is a steel material with excellent workability.
2. A steel material with excellent workability as described in claim 1, wherein the spheroidization rate of the carbides having a grain size of 150 nm or more is 95% or more.
3. 2. The steel material having excellent workability according to claim 1, wherein the room temperature surface hardness of the steel material is 230 to 270 HV.
4. The steel material has a burr height of 20 μm or less after press working, 2. The steel material having excellent workability according to claim 1, wherein the bending workability (R / t) of the steel material is 2 or less.
5. 2. A steel material with excellent workability according to claim 1, wherein the average grain size of the carbides is 0.55 μm or more.
6. A steel material having excellent workability, the steel material having a surface hardness of 56 HRC or more after being heated to 800 to 950°C and maintained for 30 minutes or less, cooled to a temperature range of 50°C or less at a cooling rate of 50 to 150°C / s, and heat-treated at 200 to 300°C for 10 to 60 minutes.
7. reheating, hot rolling, and coiling a slab containing, by weight percent, 0.8-1.0% C, 0.1-0.3% Si, 0.2-0.5% Mn, 0.1-0.3% Cr, 0.03% or less P, and 0.005% or less S, with the balance being Fe and other unavoidable impurities; applying a mechanical force to the wound steel material to segment carbides of the steel material; and then maintaining the steel material having the carbides in a temperature range of 650 to 700° C. for 5 to 20 hours to perform spheroidizing annealing.
8. 8. A method for producing a steel material with excellent workability according to claim 7, wherein in the step of segmenting the carbides, the coiled steel material is cold-rolled at a rolling reduction of 30 to 50% to segment the carbides of the steel material.
9. Reheating the slab at a temperature in the range of 1000 to 1300°C; hot rolling the reheated slab in the temperature range of 850 to 1150°C; The method for producing a steel material having excellent workability according to claim 7, wherein the hot-rolled steel material is coiled in a temperature range of 600 to 650°C.
Citation Information
Patent Citations
Manufacture of high-carbon sheet metal having superior formability
JP1990101122A
Carbon steel sheet excellent in fine blankability
JP2000265240A
High toughness high carbon steel sheet having excellent workability, and production method therefor
JP2003147485A
Spheroidization annealing method for manufacuring high carbon steel sheet having exceelent farmability and high carbon steel sheet produced by the same
KR1020150075290A